Energy dispersive anti-anharmonic effect in a Fano intervened semiconductor: revealed through temperature and wavelength-dependent Raman scattering. Issue 3 (5th January 2023) - Rani, Chanchal; Kandpal, Suchita; Ghosh, Tanushree; Bansal, Love; Tanwar, Manushree; Kumar, Rajesh
Abstract : Dissociation energy taken to break the electron-phonon bound state (Fano-interferons) varies with excitation photon energy. The Fano interaction weakens by decreasing wavelength or increasing temperature as seen in the Raman thermal map. Abstract : It is always interesting to understand how the interplay between two perturbations, affects any physical process and gets manifested in a semiconductor. Temperature- and wavelength-dependent Raman Spectromicroscopy was performed on heavily-doped Si to reveal an unusual anti-anharmonic effect. Additionally, the energy dispersive behaviour of Fano coupling strength was also studied and its possible interrelation with the observed anti-anharmonic effect was explored. A systematic study revealed that at the different excitation wavelengths, the strength of the Fano interaction was different, where the involved electron–phonon (Fano-Fano-interferon) bound states were counted together with different energies. By understanding how the interplay manifests in terms of the Raman line shape, a method to calculate the Fano-interferon dissociation energy was developed. The slope of the Raman linewidth at different excitation wavelengths with temperature showed a negative temperature coefficient and sign reversal on decreasing the doping concentration. A wavelength-dependent empirical relation is proposed to calculate the required thermal energy, required to dissociate the electron–phonon bound state.